Hubungan Kelekatan Aman Orang Tua terhadap Krisis Seperempat Kehidupan Pemuda Anggota Karang Taruna di Desa Siwalan Panji Sidoarjo - Luthfiana, Anisa; Hazim, Hazim (LPPM Institut Pendidikan Nusantara Global, 2025)
The phenomenon of quarter-life crisis (QLC) has gained attention in the context of early adulthood psychological development, particularly in relation to the role of parental attachment as a potential protective factor. This study aims to examine the relationship between secure parental attachment and QLC among members of the Karang Taruna youth organization in Siwalan Panji Village, Sidoarjo. This is a quantitative study with a correlational approach, involving the entire population of Karang Taruna members aged 20–30 years, totaling 75 individuals, selected through a saturated sampling technique. The instruments used include the Secure Parental Attachment Scale and the Quarter-Life Crisis Scale, with reliability scores of 0.861 and 0.914, respectively. Data were analyzed using simple linear regression with the help of SPSS version 25, through normality, linearity, and significance tests. The results showed that secure attachment is significantly and negatively correlated with QLC (p < 0.001), with a contribution rate of 67.1%. In conclusion, the higher the level of secure parental attachment, the lower the risk of experiencing QLC. The study suggests developing intervention models based on parental attachment to support youth psychological well-being.